Hydrogen embrittlement of high strength steel under in situ corrosive charging conditions and tensile load. Issue 1 (21st June 2016) - Scharf, R.; Muhr, A.; Stellnberger, K.‐H.; Faderl, J.; Holzer, C.; Mori, G.
Abstract : It is known that advanced and ultra‐high strength steel grades (AHSS and UHSS) are susceptible to hydrogen embrittlement under certain test conditions1 2 . In this study, punched hole specimens for constant load testing with in situ hydrogen charging were used to quantify the effect of different corrosive conditions. Flowing or stagnant electrolyte (5% NaCl) conditions were established and time to failure was recorded as a function of applied tensile stress. The pH of the solution was set at 2, 7, and 12. Bare and zinc‐galvanized (EG) specimens were used. Hydrogen uptake as a function of immersion time was characterized. Abstract : In this study, punched hole specimens of ultra‐high strength steel grades for constant load testing with in situ hydrogen charging were used to quantify the effect of different corrosive conditions. Fluent or stagnant electrolyte (5% NaCl, pH 2, 7, and 12) conditions were established and time to failure was recorded as a function of applied tensile stress. Bare and electrolytically galvanized specimens were used.